The effect of drought on energy and water vapour exchange above a mediterranean C3/C4 grassland in Southern Portugal - Aires, L.M. (2008)
We studied the seasonal and interannual variation in surface energy fluxes – net radiation (Rn), soil heat (G), sensible heat (H) and latent heat (lE) fluxes – and water vapour exchange above a Mediterranean C3/C4 grassland in Portugal, during two hydrological years, i.e., the period from 1 October to 30 September of the next year, of contrasting rainfall. The first year, 2004–2005, was dry, with total precipitation 45% below the long-term mean (669 mm), whereas the following, 2005–2006, was normal, with total precipitation only 12% above the long-term mean. Soil water availability and plant canopy growth were the most important factors in determining the seasonal and interannual variation in energy partitioning. During autumn, winter and early spring the ratio lE/Rn dominated over H/Rn, in the two years of the study, whereas on an annual basis, the major portion of Rn was consumed in H and lE in the dry and normal years, respectively. The total annual evapotranspiration (E) and its daily maximum were 316 mmand 2.8 mmper day, respectively, for the dry year, and 481mmand 4.5 mmper day for the normal year. After the senescence of the C3 species, the warm-season perennial C4 grass, Cynodon dactylon L., played a preponderant role in maintaining substantial E rates contributing to soil water depletion. In this study, we assessed the effects of the most relevant biophysical factors on surface conductance (gs) and E.We found that the Priestley–Taylor coefficient and gs were substantially reduced when the average volumetric soil moisture content in the top 15 cm of the soil profile dropped below 14%. With abundant soil moisture and leaf area index (LAI) greater than 1, the evaporative fractions (lE/Rn) were linearly related to LAI (R2 = 0.73). The decoupling coefficient (V) ranged from a maximum of about 0.7, under non-limiting soil moisture conditions, to a minimumof about 0.1, under soil moisture deficit. This suggests that E was strongly controlled by the vapour pressure deficit of the air and gs during the periods with limiting soil moisture.